Dynamics of Vitellogenin and Vitellogenesis-Inhibiting Hormone Levels in Adult and Subadult Whiteleg Shrimp, Litopenaeus vannamei: Relation to Molting and Eyestalk Ablation. Issue 1 (1st January 2014) - Kang, Bong Jung; Okutsu, Tomoyuki; Tsutsui, Naoaki; Shinji, Junpei; Bae, Sun-Hye; Wilder, Marcy N.
Abstract: Levels of vitellogenin (VG) and vitellogenesis-inhibiting hormone (VIH) in the whiteleg shrimp, Litopenaeus vannamei, were measured by time-resolved fluoroimmunoassay in relation to the molting cycle and ovarian maturation induced by eyestalk ablation. During the molt cycle, VG mRNA expression levels and VG concentrations showed similar patterns of fluctuation. VG levels increased significantly at early intermolt (stage C0) in adults, but not in subadults. Unilateral and bilateral eyestalk ablation increased VG levels in adults, whereas only bilateral eyestalk ablation affected subadults. VIH levels showed contrasting patterns between adults and subadults. In adults, levels were high in late postmolt adults (stage B) and then low thereafter, whereas they increased from postmolt (stage A) to intermolt (stage C0) in subadults and remained high. Unilateral eyestalk ablation increased VIH levels 10 days following ablation in adults, after which levels decreased at 20 days. VIH levels decreased from 10 to 20 days after bilateral ablation. Both unilateral and bilateral ablation led to increased VIH levels in subadults. Eyestalk ablation induced ovarian maturation, but did not reduce VIH concentrations in the hemolymph. This phenomenon was perhaps due to other crustacean hyperglycemic hormone peptides having cross-reactivity with VIH antibodies. This is the first report to quantify concentrations of VG and VIH together in L. vannamei hemolymph, and to examine their relative dynamics.